2010
DOI: 10.1002/anie.201004318
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorophenyl Derivatives of La@C3v(7)‐C82: Endohedral Metal Induced Localization of Pyramidalization and Spin on a Triple‐Hexagon Junction

Abstract: Core controls shell: The X‐ray structure of a dichlorophenyl adduct of the unprecedented La@C3v(7)‐C82 shows that the substituent is singly bonded to a triple‐hexagon junction C atom, which has pronounced radical character due to strong metal–cage interactions, revealed by plotting theoretical p‐orbital axis vector (POAV) values against SOMO spin densities for the different types of C atoms (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 58 publications
0
48
0
7
Order By: Relevance
“…[1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82. [1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82.…”
mentioning
confidence: 99%
“…[1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82. [1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82.…”
mentioning
confidence: 99%
“…Soon after, corresponding derivatives of La@C 82 were also obtained 23. The results were also surprising because, in theory, the obtained isomer La@ C 3v (7)‐C 82 is not the most stable one among all possible isomers of C 82 when encapsulating a La atom: C 3v (8)‐C 82 is 16.1 kcal/mol more stable.…”
Section: Structural Elucidation Of Emfsmentioning
confidence: 98%
“…[116] Danach wurden die elektrochemischen Eigenschaften von #1809 C 60 Cl 8 untersucht und mit denen von #271 C 50 Cl 10 verglichen, was sein besonderes elektroaktives Polymerisationsverhalten aufzeigte,d as sich deutlich von dem der Chloride von I h -C 60 wie C 60 Cl 8 und C 60 Cl 10 unterschied. [117] Kürzlich synthetisierten Tr oyanov et al durch Anwendung einer Nachchlorierungsreaktion von I h -C 60 mit SbCl 5 drei neue Nicht-IPR-Chloride von C 60 -C 2v -#1810 C 60 Cl 24 , D 2d -#1805 C 60 Cl 24 und D 5 -#1794 C 60 Cl 20 -m it vier, vier bzw.f ünf DFP-Paaren (Abbildung 8e-g), zusammen mit einem nichtklassischen Nicht-IPR-Derivat von C 60 , [131] 66 in zwei Te ile, in einen halbkugelfçrmigen C 50 -Teil und einen benzolähnlichen C 6 -Ring mit sp 2 -Kohlenstoffatomen, wodurch die lokale Aromatizitätverringert werden kann. [36] Mit dem gleichen modifizierten Bogenentladungsverfahren mit CCl 4 synthetisierten und isolierten Xie et al außerdem C 68 Cl 6 .…”
Section: Angewandte Chemieunclassified
“…[10] Die korrigierte Molekülstruktur von Sc 2 @C 66 wurde 2014 von Akasaka et al auf Basis einer Untersuchung mittels Einkristall-Rçntgenbeugung und zweidimensionaler INADEQUATE-NMR-Spektroskopie bestimmt, die eindeutig das Vorhandensein von zwei TFP-S-Gruppierungen am Nicht-IPR-Käfig C 2v (4059)-C 66 zeigten. [11] Interessant ist, dass die beiden eingeschlossenen Scandiumionen innerhalb von Sc 2 @C 2v (4059)-C 66…”
Section: Stabilisierung Von Tfp üBer Endohedrale Fullereneunclassified
See 1 more Smart Citation